2012
DOI: 10.1136/heartjnl-2011-301411
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine plasma level and A2Aadenosine receptor expression: correlation with laboratory tests in patients with neurally mediated syncope

Abstract: These findings indicate that patients with NMS present different purinergic profiles and that responses to HUT and ATP are correlated with these profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 25 publications
3
33
0
7
Order By: Relevance
“…High APC was previously repeorted in VVS [3,16]. This high APC is responsible for the drop in blood pressure and loss of consciousness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High APC was previously repeorted in VVS [3,16]. This high APC is responsible for the drop in blood pressure and loss of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Their VVS state was well documented by previous head-up tilt test (a test that reproduce the symptomatology), [15] and were recruited in the department of cardiology of the Timone hospital. Patients were included to have a broad range of APC range, because VVS patients are known to have basal high APC [16]. Healthy subjects and patients gave their written inform consent for blood collection.…”
Section: Blood Samplesmentioning
confidence: 99%
“…Those assigned to dual chamber pacing had fewer syncopal episodes during follow-up (32% absolute and 57% relative reduction in syncope). A positive test with intravenous adenosine 50-triphosphate (ATP) has been shown to correlate with a subset of patients with neurally mediated syncope (84). A randomised, multicentre trial of the potential benefit of the ATP test in elderly patients (mean age 75.9±7.7 years) with syncope of unknown origin reported that active dual chamber pacing in those with a positive ATP test reduced syncope recurrence risk by 75% (95% CI 44% to 88%) (85).…”
Section: Heart Block and Pacemakersmentioning
confidence: 99%
“…Thus, a different basal APL profile seems to be present in patients with idiopathic AV block and in patients with vasovagal syncope. [9][10][11] Finally, permanent cardiac pacing is successful in preventing syncopal recurrences during long-term follow-up in idiopathic AV block patients but much less effective in patients affected by reflex cardioinhibitory syncope, even if a spontaneous asystolic reflex has been documented, with syncope recurring in 9% to 45% of patients. 5,12 The cause of persistence of syncopal recurrence in reflex syncope is attributed to the coexistence of a vasodepressor reflex which, to some degree, is present in virtually all patients.…”
Section: Box 1 Definitionsmentioning
confidence: 99%
“…The adenosine/ATP test seemed to be sensitive enough to identify the patients with idiopathic AV block in this study, but it showed a very low specificity in other studies in which there was a lack of correlation between the responses to the test and the mechanism of spontaneous syncope documented by ILR. 11,12 The ability of APL value to discriminate idiopathic AV block cases from vasovagal syncope patients was evaluated using receiver operating characteristic curve analysis (Deharo JC et al, personal communication, 2013). A cutoff value of APL of 0.38 was found to have a sensitivity of 61% and a specificity of 92%.…”
Section: Clinical Perspectivesmentioning
confidence: 99%